1992
DOI: 10.1007/bf01129966
|View full text |Cite
|
Sign up to set email alerts
|

Topographical changes in the ongoing EEG related to the difficulty of mental tasks

Abstract: An experiment was carried out to investigate the hypothesis that task difficulty is reflected in changes in the topographical distribution of the ongoing EEG. Subjects had to perform three different tasks at two difficulty levels each; the Sternberg memory scanning task in an auditory and in a visual mode and a task whose performance required mainly visual scanning. Task difficulty was verified by the measurement of response times. Using a commercial Brain Electrical Activity Mapping device, EEG was recorded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
1
18

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(126 citation statements)
references
References 23 publications
11
96
1
18
Order By: Relevance
“…Decreased alpha in the high-load task is consistent with the notion that the amplitude of this signal is inversely related to the proportion of cortical neurons involved with task performance. Similar patterns of effort-related modulation of the EEG have been found in numerous other investigations (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Although spectral components of healthy adults' EEG have been shown to be sensitive to the mental effort associated with computer-based laboratory tasks, few data exist concerning whether the EEGs of juvenile subjects playing commercial video games will exhibit the similar patterns.…”
mentioning
confidence: 74%
“…Decreased alpha in the high-load task is consistent with the notion that the amplitude of this signal is inversely related to the proportion of cortical neurons involved with task performance. Similar patterns of effort-related modulation of the EEG have been found in numerous other investigations (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Although spectral components of healthy adults' EEG have been shown to be sensitive to the mental effort associated with computer-based laboratory tasks, few data exist concerning whether the EEGs of juvenile subjects playing commercial video games will exhibit the similar patterns.…”
mentioning
confidence: 74%
“…Heart rate is useful to determine the operator's global response to task demands (Wilson & Eggemeier, 1991). The electroencephalogram (EEC) provides useful information about both high workload and inattention (Gundel & Wilson, 1992;Kramer, 1991;Steman & Mann, 1995;Wilson & Eggemeier, 1991). EEG measures have been used to classify patients with regard to types of neuropathy and psychiatric disorders using linear statistical techniques (John, Pricep, Fridman, & Easton, 1988) and artificial neural networks (ANNs; Kloppel, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Klimesch has suggested that theta synchronisation reflects the introduction of cortical activation via cortico-hippocampal feedback loops, and has demonstrated that task-related increases in theta power are related to the successful encoding of new information in episodic memory [31,173]. Increases in theta are typically associated with increases in mental workload as defined by task difficulty and stimulus complexity [184], whereas decreased theta is found to be associated with incorrect responses on a signal detection task [185] or when tasks become more familiar or easier [186].…”
Section: Theta Activity (Indexed By Theta Spectral Components)mentioning
confidence: 99%
“…Frontal midline theta has been reported to increase with increased memory load and workload in general [186,[189][190][191], mental concentration [165,166,[192][193][194], focused attention [129,184,195] and serves a response controlling function [151].…”
Section: Theta Activity (Indexed By Theta Spectral Components)mentioning
confidence: 99%